Field notes contributed by Aaron Brees, fall 1997 - Brees, Aaronet al (1997)
Fall report of birds and locations contributed by Aaron Brees. Also includes a brief note from Brees to Thomas H. Kent regarding the lateness of the report. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1997. Epson - sheet feed/flatbed